Intelligent design of street lamp based on Arduino. Issue 5 (July 2020) - Liu, Yuanchao; Zheng, Kuncan; Liu, Yuanhao; Wu, Tao; Zhao, Xudong
Abstract: In order to promote the process of social modernization, the traditional street lamps are also moving towards intelligent development. However, the existing street lamps mostly use a single LED lamp or high-pressure sodium lamp, which can't cope with the complex road conditions in China. The designer proposes to install the monitoring system on the street lamp, design the fine artificial intelligence light distribution and color temperature regulation scheme, add the functions of positioning, alarm, repair, pollutant and rain and snow monitoring, and realize the data interaction between the street lamp and the user and the manual intervention of the user when necessary through the infrared Bluetooth Internet of things and other technologies. The design is developed, simulated, debugged and tested on Arduino hardware and software platform. The results show that the design is reasonable and feasible.